Iron Overload Reduces Cholestrol and Triglyceride Serum of Mice - Setiawati, Devi Agustin; Syamsunarno, Mas Rizky A.A.; Fianza, Pandji Irani; Atik, Nur; Anggraeini, Neni; Ghozali, Mohammad; Safitri, Ratu; Panigoro, Ramdan (KnE Life Sciences, 2017)
Most of the case of patient with hemoglobin disorder genes need routine blood transfusion throughout their life. It leads to increase iron accumulation with liver as the main organ for iron storage. Liver is the main organ for metabolic process, including triglyceride and cholesterol. However, correlation between metabolism of triglyceride and cholesterol, and iron overload condition is remain uncertain. The purpose of this study was to investigate the effect of iron overload to triglyceride and cholesterol level in the serum of mice. Keywords: iron overload; Triglyceride serum; Cholesterol Serum.